Colorimetric Detection of Ammonia Using Synthesized Silver Nanoparticles from Durian Fruit Shell. (20th October 2020) - Alzahrani, Eman
Abstract : There has been increased interest in the production of nanoparticles (NP) through green chemistry. This article used durian fruit shell aqueous solution that acts as a reductive preparation of silver NPs. The silver nanoparticles have a size of approximately 25 nm. The NP size uniformity was determined by the SEM and TEM analysis. X-ray diffraction technique was used to characterize crystalline silver nanoparticles face-centered cubic structure. XPS spectrum showed distinct silver peaks on the nanoparticles' surface. An optical method that was based on surface plasmon resonance (SPR) was used to perform the green Ag NPs aqueous ammonia sensing study. Optical measurement facilitated the ammonia sensing study of Ag NPs that had been prepared. The study also investigated the performance of the optical sensor, thus adding validity to the study. Also, the research sought to determine how the concentration of ammonia in ammonia sensing affects the Ag NPs that had been obtained. The study observed a linear relationship with R 2 as the correlation factor which was equal to 0.9831. This was observed from the ammonia concentration plot versus absorption ratio that suggested that there was a linear increase in absorption ratio with increase in ammonia concentration. The study significance is that the room temperature optical ammonia sensor can be used in future for medical diagnosis in the detection of low levels of ammonia in biological fluid like sweat, cerebrospinal fluid, saliva, plasma, or biological samples. This enhances the application of the technique in human biomedical applications.